Do Subsidized Health Programs in Armenia Increase Utilization among the Poor? - Angel-Urdinola, Diego (2012)
This article analyzes the extent to which the Basic Benefit Package (BBP), a subsidized health program in Armenia, increases utilization and affordability of outpatient health care among the poor. We find that beneficiaries of the BBP pay approximately 45 % less in fees for doctor visits (and display 36 % higher outpatient utilization rates) than eligible users not receiving the BBP. However, even among BBP beneficiaries the level of outpatient health care utilization remains low. This occurs because the program mainly provides discounted fees for doctor visits, but fees do not constitute the main financial constraint for users. Our estimates suggest that other non-fee expenditures, such as prescription medicines, constitute a more significant financial constraint and are not subsidized by the BBP. As a result, outpatient health care remains expensive even for BBP beneficiaries.